2018
DOI: 10.1002/ange.201812167
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Reactions of Pyridines To Give Ring‐Fused Pyridiniums: In Situ Activation Strategy Using 1,2‐Dichloroethane as a Vinyl Equivalent

Abstract: Reported herein is a rhodium(III)‐catalyzed three‐component annulation reaction of simple pyridines, alkynes, and 1,2‐dichloroethane (DCE), affording a streamlined pathway to diverse ring‐fused pyridiniums. DCE not only serves as a vinyl equivalent but also as an in situ activating agent for pyridine C2−H activation. A cationic five‐membered rhodacycle complex has been isolated and proposed as a possible intermediate. This strategy can be extended to other N‐containing heteroarenes for the synthesis of multiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Ionic fluorophores such as multiring‐fused pyridinium ions, particularly interesting as bio‐markers, have been undergoing massive explorations over the past decade, the synthetic strategies of which were extremely complicated and demanded some prefabricated molecules. Gratifyingly, the introduction of MCRs enabled Wang and co‐workers in 2018 to design a Rh(III)‐catalyzed annulation reaction of simple substrates such as pyridines, alkynes and 1,2‐dichloroethanes ( Scheme ) . When the reaction was examined to understand the diverse substrate scope of alkynes, it was observed that diaryl as well as dialkyl alkynes, regardless of the functional group, fitted well to give moderate to good yield.…”
Section: Rhodium‐catalysed Multi‐component Reactionsmentioning
confidence: 99%
“…Ionic fluorophores such as multiring‐fused pyridinium ions, particularly interesting as bio‐markers, have been undergoing massive explorations over the past decade, the synthetic strategies of which were extremely complicated and demanded some prefabricated molecules. Gratifyingly, the introduction of MCRs enabled Wang and co‐workers in 2018 to design a Rh(III)‐catalyzed annulation reaction of simple substrates such as pyridines, alkynes and 1,2‐dichloroethanes ( Scheme ) . When the reaction was examined to understand the diverse substrate scope of alkynes, it was observed that diaryl as well as dialkyl alkynes, regardless of the functional group, fitted well to give moderate to good yield.…”
Section: Rhodium‐catalysed Multi‐component Reactionsmentioning
confidence: 99%
“…In recent years, multicomponent reactions are becoming a significant tool for synthesizing biologically impactful heterocycles, heterocyclic scaffolds under sustainable reaction conditions, N ‐heterocyclic carbenes, ring‐fused pyridiniums, 1,4,5‐trisubstituted 1,2,3‐triazoles, and small “drug‐like” structures in medicinal chemistry, in addition to structurally complex molecules with interesting biological aspects, drug detection, and materials science as they furnish the desired products in a single procedure . These reactions are carried out easily to construct numerous target molecules from the starting materials in good to excellent yields without isolating the intermediates, thus minimizing the number of synthetic stages, avoiding the wastage of chemicals, and saving energy consumption and time.…”
Section: Introductionmentioning
confidence: 99%